ADDITION OF BENDRAT WIRE TO THE FIBER CONCRETE MIXTURE WITH ARTIFICIAL COARSE AGGREGATE MADE FROM TANGKILING CLAY, PALANGKA RAYA CITY - Liliana; Abertun Sagit Sahay; Supiyan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study evaluates the physical properties, bulk density, water absorption, and specific gravity of artificial coarse aggregate derived from Tangkiling clay, Palangka Raya City, as well as the effect of wire fiber addition on the mechanical properties of fiber concrete. The artificial coarse aggregate was produced by firing clay at a temperature of 1000°C, resulting in rounded aggregate shapes. The bulk density of the aggregate in a loose condition was recorded at 889 kg/m³, while the water absorption was 13.69%. The specific gravity in dry and saturated surface-dry conditions was 1.260 and 1.385, respectively. The fiber concrete made with a combination of artificial coarse aggregate and wire fiber showed a hardened concrete bulk density ranging from 1890 – 2070 kg/m³. The optimal wire fiber concentration of 1.93% produced a maximum compressive strength of 20.399 MPa. However, statistical analysis revealed that the addition of wire fiber had no significant effect on increasing the compressive strength.